Performance of sorghum varieties with various fertilizer doses in peatlands of West Aceh Regency: - Andriani, Dewi; Irawan, Jekki; Syahputra, Iwandika; Arisma Siregar, Mawaddah Putri; Sari, Putri Mustika (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2024)
West Aceh Regency is one of the regions in Indonesia with quite extensive peatlands, but the diversity of food crop commodities is still very low. To enhance food diversification programs of rice, sorghum production is important. The purpose of this research was to test several varieties of sorghum in the peatlands of West Aceh Regency. This research was carried out from July to November 2023. Several new varieties of sorghum released by the Indonesian Cereals Research Institute (ICERI) were evaluated in the peatland of West Aceh. The research method used a randomized complete block design (RCBD) with two factors and three replications. The first factor was different varieties of sorghum, and the second factor was various doses of fertilizers. The varieties used were Soper 7 Agritan, Bioguma 1, and Suri 3. The doses used Control (no treatment), Dose I (75 kg Urea ha-1 + 50 kg SP-36 ha-1 + 50 kg KCl ha-1), Dose II (150 kg Urea ha-1 + 100 kg SP-36 ha-1 + 100 kg KCl ha-1), and Dose III (225 kg Urea ha-1 + 150 kg SP-36 ha-1 + 150 kg KCl ha-1). The results showed that the Bioguma 1 variety adapted better than the other varieties, where the plant height was 187.97 cm, the number of leaves was 15.08, the panicle diameter was 35.92 mm, and the panicle weight was 79.52 g. Meanwhile, fertilizer dose II is better on the character of the number of leaves and panicle length. The interaction effect between the two factors only showed a significant influence on panicle length. Therefore, the Bioguma 1 sorghum variety can be a recommended variety for planting in the shallow peatlands of West Aceh. Keywords: Acidic soil; alternative food; food diversification